Qualitative analysis on perceived satisfaction in a b-learning program at a Portuguese University - Quintas, Célia; Teixeira, Ana Luísa; Silva, Isabel Fernandes; Duarte, Jane Rodrigues (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Knowledge management and learning are buzzwords in today’s society, both in terms of company competitiveness as well as in terms of education. Human resources are thus a priority for individuals and companies. The concept of knowledge management and of learning organizations has been object of increased interest by managers and scholars. The increased focus on these issues brings forth the individual as a crucial element in this process; individuals become key elements in competitiveness (Nonaka & Takeuchi: 1995) and protagonists of their own learning process (Senge: 1992). Additionally, the learning methodologies and strategies have also changed in the past decades, so that currently much is offered by means of b-learning and e-learning courses that, on the one hand, allow students to opt for several learning strategies, and on the other hand, require them to actively participate in their learning path. In fact, the evolution of ICT in studies and the growing experience of both teachers and students have gradually adapted to new methodologies. However, while materials and subject matter have been made easier and more accessible to students who do not attend classroom sessions, an underlying problem has always been present: bridging the physical distance among all the stakeholders involved in the learning process and all the difficulties that may emerge from this. Since its first edition in 2001, this Post-Graduation Program, now in its 12th edition, has undergone several changes, from its study plan to learning regime. As a means of responding to the demands of today’s market and in particular new learning styles, new possibilities have been made for attending the course which range from classroom, to blending and e-learning formats. As a means of fostering group spirit, synchronous and asynchronous participation of all students several changes were introduced this academic year. Besides the use of the Moodle platform, a Virtual Learning Environment (VLE) wiziq has been introduced. In 2013-14, the program includes students from Portugal (including the Azores), Mexico and Nigeria. Moreover, this Post-Graduation Program allows students to opt for f2f, b-learning and e-learning regimes, i.e., within the same group, some students attend classes by means of a VLE, others attend some classes f2f and others using the VLE and others attend f2f classes regularly, though they also have access to the VLE. A program that combines three learning approaches/methodologies/strategies allows the possibility of assessing possible differences in terms of efficiency of these three learning methodologies, considering that these imply a change in expectations, attitude and cognitive process. Our paper focuses on a study carried out in a Post-Graduation Program at a Portuguese university, on perceived satisfaction regarding the use of ICT tools in the program, a theme which has already been object of study at UAL in recent years, both in terms of assessing and monitoring learning progress, of learner attitude toward their learning paths (Fernandes Silva & Rodrigues Duarte. 2011a & b) and the tools and methodologies made available to them and of perceived satisfaction (Fernandes Silva & Quintas: 2013). This paper corresponds to a 1st stage of a broader study that will involve all students in the referred program in 2013-14 as well as all the lecturers. Initially, a qualitative analysis is carried out based on semi-structured interviews; at a 2nd stage, we aim to create a questionnaire to be applied to a wider population.